In Vitro Anti-Inflammatory Evaluation of Sesbania Procumbens Extracts: Pharmaceutical Science-Pharmacognosy & Phtochemistry - Leslie, V.; Singh, Gurfateh; Aron, S.; Harikumar, S. L. (International Journal of Life Science and Pharma Research, 2022)
Plants used in the traditional healing system require a systematic evaluation that may give more promising data about their medicinal value and may be useful to meet the rising demand for novel agents to combat infections and diseases. The plant Sesbania procumbens is a one used traditionally by the rural population for a varietyof medicinal purposes including antiinflammatory activity. Based on this report the plant S. procumbens was selected for our research and in this study different extracts of S. procumbens were evaluated in vitro for anti-inflammatory activity. The whole plant material was collected, authenticated, aerial parts were separated, shade dried for about two weeks and made into a coarse powder by using mechanical grinder. Extraction of powdered material was done by soxhlation using the different solvents of increasing polarity viz., petroleum ether, chloroform, ethyl acetate and methanol. Dried extracts thus obtained were subjected to in vitro anti-inflammatory evaluation by human red blood cell (HRBC) membrane stabilization in normal and different temperature (54°C and −10°C) and tonicity (hypotonic and isotonic) conditions. Six different concentrations (100, 200, 400, 600, 800, 1000μg/ml) of four extracts were subjected to evaluation with indomethacin (100μg/ml) as standard control. The data thus collected was analysed by using SPSS version 15.0. All values are expressed as mean ± SD. P<0.05 was considered statistically significant From the results, a dose-dependent rise in antiinflammatory activity was found in all the tested extracts. Particularly, the methanol and ethyl acetate extracts showed significant activity in their maximum testing concentration (1000µg/ml) in all the experimental approaches. The results of this study strongly supported the claims of the anti-inflammatory property of the tested extracts. Further studies such as in vivo evaluations and phytochemical screening of the extracts may give more significant data which may be useful for the development of novel chemotherapeutic agents